Mapping the suitability of rice and other crops in the Mekong Mega Delta - Villano, Lorena; Raviz, Jeny; Aunario, Jorrel; Rala, Arnel; Balanza, Jane Girly C.; Bui Tan Yen; Vu Manh Quyet; Laborte, Alice G. (International Rice Research Institute, 2023)
The Mekong Delta is an important food production zone supplying rice for domestic and export markets. It is, however, highly vulnerable to the impacts of climate change. More frequent and more intense floods, salinization, water shortages and climate extremes are expected to affect the livelihood of farmers in the region. As part of the CGIAR’s Asian Mega-Deltas Research Initiative, we are exploring promising options with farmers to accelerate the adoption of diversified production systems that are better adapted to the effects of climate change. Suitability maps developed for each crop can be used to assess where and when crops would be most suitable for production and to identify and target adaptation recommendations for sustainable, resilient and productive agri-food systems in the Delta.